2021
DOI: 10.1080/07448481.2021.1978463
|View full text |Cite
|
Sign up to set email alerts
|

Mindful self-care and resilience in first-year undergraduate students

Abstract: The current study investigates mindful self-care and resilience as predictors of flourishing in first-year undergraduate students. Mindful self-care includes a) mindful awareness and assessment of one's internal needs and external demands and b) intentional engagement in specific practices of self-care to address needs and demands in a manner that serves one's wellbeing and personal effectiveness. Mindful self-care has been shown to reduce stress in postsecondary students enrolled in a medical degree. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 125 publications
(169 reference statements)
1
3
0
3
Order By: Relevance
“…Engagement in mindful self-care practices, which encompasses six domains of self-care (mindful relaxation, physical care, self-compassion and purpose, supportive relationships, supportive structure, and mindful awareness; Hotchkiss & Cook-Cottone, 2019 ), was shown to increase the likelihood of pregnant women reporting complete mental health. These results are consistent with previous studies that found that mindful self-care was negatively associated with depressive symptoms among pregnant women (e.g., Webb et al, 2019 ) and with studies conducted among the general population that have found that mindful self-care is positively associated with flourishing ( McGuinness & Nordstokke, 2021 ). Although there is evidence showing the protective role of self-compassion against psychological distress for the mother and child during the COVID-19 pandemic ( Davis et al, 2021 ), mindful self-care practices have not been studied in this context.…”
Section: Discussionsupporting
confidence: 93%
“…Engagement in mindful self-care practices, which encompasses six domains of self-care (mindful relaxation, physical care, self-compassion and purpose, supportive relationships, supportive structure, and mindful awareness; Hotchkiss & Cook-Cottone, 2019 ), was shown to increase the likelihood of pregnant women reporting complete mental health. These results are consistent with previous studies that found that mindful self-care was negatively associated with depressive symptoms among pregnant women (e.g., Webb et al, 2019 ) and with studies conducted among the general population that have found that mindful self-care is positively associated with flourishing ( McGuinness & Nordstokke, 2021 ). Although there is evidence showing the protective role of self-compassion against psychological distress for the mother and child during the COVID-19 pandemic ( Davis et al, 2021 ), mindful self-care practices have not been studied in this context.…”
Section: Discussionsupporting
confidence: 93%
“…Dalam penelitian ini, Resiliensi Taruna Akademi Militer memiliki korelasi positif terhadap attention inhibition dan response inhibition. Hasil ini juga mengonfirmasi penelitian terdahulu mengenai hubungan positif antara inhibitory control dengan resiliensi (Davidovich et al, 2016;McKee, 2017). Sehingga, semakin tinggi kemampuan inhibitory control Taruna maka semakin tinggi kemampuan resiliensinya.…”
Section: Resiliensiunclassified
“…Penelitian terdahulu menjelaskan bahwa kemampuan resiliensi memiliki korelasi yang positif dengan kemampuan inhibitory control, semakin tinggi kemampuan inhibisi seseorang maka semakin tinggi kemampuan resiliensinya (McKee, 2017). Hasil penelitian menyebutkan bahwa remaja dengan kemampuan inhibitory control yang lebih tinggi memiliki simtom depresi yang lebih sedikit dibandingkan dengan remaja yang memiliki kemampuan inhibitory control yang lebih rendah, bersama dengan mental flexibility (Davidovich et al, 2016).…”
unclassified
See 1 more Smart Citation
“…Supports specific to a postsecondary context (e.g., support from faculty or staff, support received on campus) showed a protective effect against depression in five studies across five provinces [37,38,56,57,61], a significant positive relationship with student flourishing in Alberta [36], and a significant association with reduced emotional exhaustion in Québec [39]. The source of social support may impact outcomes.…”
Section: Relevant Impacts On Wellbeingmentioning
confidence: 99%